EVALUATION OF THE MEASLES EPIDEMIOLOGICAL SURVEILLANCE SYSTEM IN DUSHANBE, TAJIKISTAN, 2023 - O.A. KHAKIMOV; Z.KH. TILLOEVA; R. HORTH; R.N. SHARIFOV; D.A. NABIROVA (Avicenna Tajik State Medical University, 2024)
Objective: To thoroughly evaluate the current measles epidemiological surveillance (ES) system in Dushanbe, Republic of Tajikistan (RT), to uncover its strong points and areas for improvement. Methods: The ES system evaluation for measles was conducted from January to May 2023 using updated guidelines from the Centers for Disease Control (CDC), USA, for ES system evaluation. Results: Upon analysis, it was found that the ES system for measles in Dushanbe functions within an overcomplicated framework that does not have proper integration with medical data systems. The current system experiences delays in sharing data at all levels; it is based on passive case detection via patient self-referral. 32.2% of patients visit urban health centers (UHC), while 67.8% go to infectious diseases hospitals. Shortcomings have been found in disseminating knowledge and implementing approved methodological recommendations by the Ministry of Health and Social Protection of the Population of the Republic of Tajikistan (MHSPP RT) in the State Sanitary Epidemiological Surveillance Service (SSESS) centers. This deficiency is due to the absence of guidelines on the Ministry's official website, the lack of a centralized repository of guidelines, and the unavailability of training platforms for epidemiologists. Although about 80% of patients have access to measles laboratory diagnostics, the system's reliance on external funding raises issues regarding its effectiveness. Insufficient human and financial resources have been identified as barriers to timely decision-making, as illustrated by the delays in rolling out mass supplementary childhood vaccinations in September 2022 following a measles outbreak detected in January 2022. Conclusion: ing out mass supplementary childhood vaccinations in September 2022 following a measles outbreak detected in January 2022. Conclusion: To achieve the country's objective of eradicating measles, the measles ES system in Dushanbe requires additional funding for emergency outbreak response. Establishing a robust training and information-sharing platform is essential to address the existing deficiencies in disseminating and implementing guidelines